Prevalence of Polypharmacy and Potentially Inappropriate Medications Use in Elderly Chinese Patients: A Systematic Review and Meta-Analysis - Tian, Fangyuan; Chen, Zhaoyan; Wu, Jinhui (Frontiers in Pharmacology, 2022)
Objectives: Polypharmacy and potentially inappropriate medication (PIM) use among elderly Chinese patients have not yet been investigated by systematic review and meta-analysis. The purposes of this study were to investigate the prevalence of polypharmacy and PIM use and the risk factors associated with PIM use in elderly Chinese patients. Methods: Databases including PubMed, EMBase, and Web of Science were searched to collect studies which used Chinese criteria, Beers criteria, or STOPP criteria to evaluate the PIM status of elderly Chinese patients from inception to August 2021 (PROSPERO Code No: CRD42021262821). Observational studies reporting the prevalence of polypharmacy and PIM use in elderly Chinese patients were meta-analyzed. The pooled prevalence and risk ratio (RR) were calculated with a 95% confidence interval (CI). Results: A total of 8 articles involving 4,558,786 patients were included. The overall prevalence of polypharmacy (concomitant use of more than 5 medicines) and PIM use pooled by meta-analysis in Chinese older patients was 48% (95% CI: 0.17, 0.79, p = 0.003) (inpatients 73%, outpatients 23%) and 39% (95% CI: 0.25, 0.54, p < 0.001) (inpatients 50%, outpatients 29%), respectively. Polypharmacy (RR: 2.03, 95% CI: 1.13, 3.64) was significantly associated with PIM use. Conclusion: This meta-analysis demonstrated a high prevalence of polypharmacy and PIM use among elderly patients in China. Affected by the quantity and quality of the included studies, the aforementioned conclusions need to be confirmed by large samples and high-quality studies.